Penyempitan Makna Ilal dalam Kritik Hadis: Kajian Kritis Pemikiran Hatim Al-Auni - Junianto, Viki; Haq, Ahmad Yusronil; Shodiq, Muhammad; Toifur, M; Hasbillah, Ahmad Ubaidy (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
In the long history of the science of hadith criticism, it can generally be divided into two phases: the riwayah phase, also known as the mutaqadimin phase, and the post-riwayah phase, also referred to as the muta'akhirin phase. According to several Muslim scholars, including Sharif Hatim al-Auni, there has been a distortion of the scientific knowledge of hadith between these two phases. This is because the mutaqadimin phase represents the application (marhalah tatbiq) of the science of hadith, while the muta'akhkhirin phase represents the theoretical (marhalah tandhir) aspect. As a result, the theories (tandhir) of the muta'akhkhirin scholars often fail to accommodate the practical applications (tatbiq) of the scholars in the mutaqadimin phase. This research aims to explain one example of this distortion, namely in the issue of 'ilal (hidden defects) in hadith. Using library research by collecting relevant data, this study concludes that there is a distortion in the interpretation of 'illat (hidden defect). The mutaqadimin scholars had a broader definition of 'illat than the muta'akhkhirin scholars.